“Read it for restoratives”: Pericles and the Romance of Whiteness - Ndiaye, Noémie (Early Theatre, 2023)
This essay reads Pericles (1608) through the lens of early modern critical whiteness studies. Tracing how the play reworks the colour-coding of its medieval source text along new racial lines, this essay sees Pericles’s melancholia as an allegory of the always incomplete condition of whiteness. It then shows how Pericles uses the erotic mechanics of romance to pursue his quest for whiteness. Ultimately, the essay underlines the relevance of Pericles’s quest to Shakespeare’s cultural moment before discussing the voices of resistance to the project of whiteness embedded within the play, and the uses of that play for our own times.